Religion in the wake of ‘total war’: Protestant and Catholic communities in Thuringia and Saxony-Anhalt, 1945-9 - Fenwick, LP (2011)
By May 1945, most major German cities lay in ruins, and a largely demoralised population struggled for subsistence in many areas. National Socialist remnants, Christian faith and communist ideology met in the rubble of the Third Reich. The Protestant and Catholic Churches attempted to ‘re-Christianise’ the Volk and reverse secularisation, while the German communists sought to inspire dynamism for their socialist project in Eastern Germany. This thesis recreates the religious world of Saxony-Anhalt and Thuringia in the Soviet zone, 1945-9, and analyses ‘religio-politics’ (the interactions between the secular authorities and the Churches), the affairs of the priesthood/pastorate, and the behaviours, mentalities and emotions of ‘ordinary people’ amongst the pews. After the American withdrawal in July 1945, the Soviet authorities occupied the entirety of Thuringia and Saxony-Anhalt, and they proclaimed a ‘freedom of religion’. The realities of this policy were different in each state, and the resolution or non-resolution of local-level disputes often determined Church and State relations. At the grassroots, though, many people engaged in a latent social revolt against all forms of authority. The Churches’ hopes of ‘re-Christianisation’ in 1945 were dashed by 1949, despite a brief and ultimately superficial ‘revival’. The majority of people did not attend church services regularly, many allegedly practiced ‘immorality’, and refused to adopt ‘Christian neighbourly love’ in helping often-destitute refugees. ‘Re-Christianisation’ also did not incur comprehensive denazification or a unified pastorate, and there was even a continuation of the Third Reich Kirchenkampf in some areas. Christian ideas of guilt for a popular turning from God, much less for Nazism and its crimes, rarely resonated amongst the population and some sections of the pastorate. This mentality encapsulated the popular rejection of authority, whether spiritual or political, that endured up to and beyond the foundation of the German Democratic Republic in October 1949.